Budaya Sekolah dalam Membentuk Student Well-Being - Nabila Paputungan; Ansar; Arifin (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze school culture in shaping student well-being at SMP Negeri 1 Gorontalo. The focus of the study includes school cultural values, artifacts or symbols of school culture, and the habituation of well-being values ​​in creating a conducive learning environment. This study uses a qualitative approach with a case study type. Data collection was conducted through interviews, observation and documentation involving the vice principal, teachers, and students as informants. Data analysis through data condensation, data presentation, and drawing conclusions. The results show that school culture at SMP Negeri 1 Gorontalo is reflected through religious values, discipline, responsibility, cooperation, mutual respect, and environmental care that are applied in daily activities at school. Cultural artifacts and symbols such as motivational slogans, school rules, moral value posters, and school environmental arrangements also support the formation of positive student behavior. Habituation activities such as morning assembly, religious activities, discipline, and cooperation among school members contribute to creating a safe, comfortable learning environment that supports student well-being. This study concludes that school culture has an important role in shaping students' social, emotional and academic well-being through the internalization of values ​​that is carried out consistently and continuously.